Effect of Hyper and Hypothyroidism on Lipid Profile and Liver Function of Male Rats (Baghdad Science Journal, 2011)
This study was designed to investigate the effect of thyroid hormone disturbance on lipids profiles and liver functions.Eighteen mature male rats Rattus norvegicus were divided into three groups. The first and the second groups were injected subcutaneously with thyroxine (T4) and carbimazol (both at 600 µg/kg BW) respectively on alternate days, to produce recurrent periods of hyper and hypothyroidism .The control group which is the third group was injected with physiological saline. The process continued 4 weeks, after that, injection, blood specimens were collected to estimate serum levels of T3 and T4, Total cholesterol (TC), Triglycerides (TG), High density lipoprotein cholesterol (HDL-C), Low density lipoprotein cholesterol (LDL-C) and Very low density lipoprotein cholesterol (VLDL-C) were determined in the serum. In addition to that, we measure GOT, GPT and CPK enzymes activity.The results showed no significant difference in body weight and a significant increase (P